2015
DOI: 10.1111/1753-0407.12347
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan combined with probucol effectively reduces urinary protein in patients with type 2 diabetes: A randomized double‐blind placebo‐controlled multicenter clinical study

Abstract: Background: Persistent proteinuria is an important factor contributing to the progression of diabetic nephropathy. The present randomized double-blind placebo-controlled multicenter clinical study evaluated the efficacy and safety of telmisartan combined with the antioxidant probucol in reducing urinary protein levels in patients with type 2 diabetes (T2D). Methods: Patients with T2D and 24-h proteinuria 0.5-3 g were enrolled in the study and randomly assigned to one of two groups: a telmisartan or a probucol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…Therefore, the study was not designed to examine the additional benefit of probucol when added to the optimized dosage of ACEIs/ARBs, and the proportion of subjects who used ACEIs/ARBs before the run-in period was not provided. 12 In the current study, probucol did not decrease the oxidized LDL level (Figure 3). However, this finding does not preclude an antioxidative effect of probucol because it has been suggested that the protective effect of probucol depends not on its ability to inhibit lipid oxidation, but on its ability to induce the stress-induced anti-inflammatory enzyme heme oxygenase-1.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…Therefore, the study was not designed to examine the additional benefit of probucol when added to the optimized dosage of ACEIs/ARBs, and the proportion of subjects who used ACEIs/ARBs before the run-in period was not provided. 12 In the current study, probucol did not decrease the oxidized LDL level (Figure 3). However, this finding does not preclude an antioxidative effect of probucol because it has been suggested that the protective effect of probucol depends not on its ability to inhibit lipid oxidation, but on its ability to induce the stress-induced anti-inflammatory enzyme heme oxygenase-1.…”
Section: Discussionsupporting
confidence: 42%
“…In a recent study that showed the superior efficacy of probucol plus telmisartan to that of telmisartan alone in terms of proteinuria extent, the dosage of probucol was 1000 mg/d (500 mg twice daily) for the first 24 weeks and then 500 mg/d (250 mg twice daily) for an additional 24 weeks. 12 The protective effect of probucol in contrast-induced acute kidney injury has also been reported [15][16][17] presumably because of the antioxidant effect of probucol. The dosage of probucol in these studies, 1000 mg orally before the procedure and then 500 mg twice daily for 3 days, was much higher than that of the current study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[ 3 ] On the other hand, the combinations of ARBs with natural products such as curcumin and resveratrol have been found to be more effective in reducing metabolic perturbation, inflammation, insulin resistance (IR), hypertension, and many other complications associated with diabetes. [ 4 5 ] Recently, we have reported that combination of telmisartan with a functional food ingredient, esculetin-prevented oxidative stress, cardiac fibrosis, and vascular stiffness in high-fat diet (HFD) induced IR condition. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%